Survey Of Public Satisfaction With Information Systems Village Fund Management In Pematang Serai Village Langkat District - Galih Supraja; Junawan, Junawan; Annisa Fajariah Damanik (CV. AFDIFAL MAJU BERKAH, 2024)
This research was carried out in Pematang Serai village, Langkat Regency. Purposeful research to provide information on the level of public satisfaction with the information system managing village funds in Pematang Serai Village, Langkat Regency. Research Model carried out using a descriptive approach with data collection techniques carried out using distributing questionnaires, observations and interviews with predetermined sources using the Slovin formula. The population in the study was 100 people with a sample 80 samples were selected using a purposive sampling approach. Analysis data was carried out using a qualitative descriptive method based on the PAN Ministerial Regulation & RB Number 14 of 2017. The results of this research show that the Satisfaction Index Pematang Serai village community regarding the management of village funds by the village government Pematang Serai produces a level of satisfaction in the